Resilience. A useful approach for climate adaptation? - Abeling, Thomas; Daschkeit, Achim; Mahrenholz, Petra; Schauser, Inke (Springer, 2018)
In der Arbeit wird vorgeschlagen, die Aspekte der Resilienz, die auf sinnvolle Weise operationalisiert werden können, in die bestehenden Konzepte der Anpassung an den Klimawandel zu integrieren.

This chapter reflects on the parallels between resilience and adaptation and discusses whether a measurable resilience concept is useful for adaptation to climate change. It argues that a focus on measurability and operationalization risks to overemphasize conservative resilience concepts focused on maintaining the status quo (resilience as robustness) while marginalizing more intangible aspects such as learning (resilience as transformation). We suggest that those aspects of resilience that can be operationalized in a meaningful way should be integrated in existing concepts of climate change adaptation such as vulnerability and adaptive capacity. The most promising value of resilience for climate adaptation, we argue, actually lies in its ability to articulate a vision for a positive future ("Leitbild"). This meaning of resilience emphasizes the relevance of vision-building and the use of participatory instruments to foster learning and innovation. It is with this vision of development that resilience is able to expand the realms of climate adaptation.
Keywords: Resilienz; Konzeption; Klimaanpassung; Anwendung; Vulnerabilität; Anpassungsfähigkeit; Monitoring; Netzwerk; Fallbeispiel; Hitze